Design and implementation of vehicle multimedia system automated test. Issue 6 (April 2019) - Xie, Peng; Du, Li; Zhou, Bing; Yu, Yongyan; Hu, Haixia; Liang, Zilong; Cui, Lianghao
Abstract: With the development of electronic vehicle, there are plenty of new functions developing on vehicle multimedia system. New technologies, such as Bluetooth, navigation, multimedia, wireless network, applying to vehicle multimedia system, are leading to more human effort. This paper describes a new method of automated test, which is adopt to test product after design. With technique of image processing and audio processing, automated test platform shows good performances at verification of vehicle multimedia system.